Cardiorespiratory fitness attenuates the association between fatness and cardiometabolic risk in Chinese children - Zhang, Ping-Ping; Wang, You-Xin; Gu, Jia-Yin; Xu, Miao; Zhou, Ye; Wang, Hai-Jun; Lau, Patrick W C.; Wang, Hui; Li, Li (Frontiers in Endocrinology, 2024)
Background Childhood obesity tends to persist into adulthood, predisposing individuals to cardiometabolic risk (CMR). This study aims to investigate the mediating role of cardiorespiratory fitness (CRF) in the associations between multiple fatness indicators and individual CMR markers and clustered CMR-score, and explore sex differences. Methods We recruited 1,557 children (age: 8 to 10, male/female: 52.7%/47.3%) in September 2022 in Ningbo, China. Physical examinations, overnight fasting blood test, and CRF was evaluated. The CMR-score was calculated by summing age- and sex-specific z scores of four CMR markers, including mean arterial blood pressure, triglycerides, the total cholesterol to high-density lipoprotein cholesterol ratio, and homeostatic model assessment for insulin resistance. Generalized linear mixed models were used to identify the associations, mediation analyses were performed to dissect the function of CRF. Results Partial correlation analyses revealed positive associations between high fatness indicators (including body mass index [BMI], BMI z score, body fat mass index [BFMI] and waist-to-height ratio [WHtR]) and increased CMR markers, whereas high CRF was associated with decreased CMR markers (all P < 0.05). In the mediation analyses, CRF emerged as a partial mediator, attenuating the relationship between four fatness indicators and CMR-score. Specifically, CRF mediated 6.5%, 7.7%, 5.3%, and 12.5% of the association between BMI, BMI z score, BFMI, WHtR and CMR-score (all P < 0.001). And the mediating effects of CRF between WHtR and four individual CMR markers was particularly robust, ranging from 10.4% to 21.1% (all P < 0.05). What’s more, CRF mediates the associations between WHtR and CMR-score more pronounced in girls than boys with a mediation effect size of 17.3% (P < 0.001). Conclusion In Chinese children, CRF partially mitigates the adverse effects of fatness on CMR, underscoring the significance of enhancing CRF in children.